Programs for the improvement of literacy: a critical reading - doi: 10.4025/actascieduc.v35i2.20634 - Cláudia Maria Mendes Gontijo (Universidade Estadual de Maringá, 2013)
The pedagogical and conceptual bases of the teachers´ formation program in Literacy and Language (Pro-literacy) for the early years of elementary education are problematized. The reduction in schooling knowledge to basic abilities found in the current evaluation reference for literacy and initial schooling of the 'Provinha Brasil' is also investigated. Results show that the reduction of the educational process to the teaching of Mathematics and Portuguese in the first years of fundamental education leads towards curriculum degradation. The reduction of literacy and language knowledge to reading is against the children's right of expression and fails to promote the quality development of schooling in Brazil.